Generation Assessment of Organic Waste with Correlation and Forecasting Models (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research objection on The data collection of the organic waste amount were produced in2016 until 2019 through 4 years , the unit is in kilogram. The organic waste divided into 2 categories which are fruit peel and food waste on center of organic management generating the bio fermented water to supply for garden of KU campus and green schools with Vertical Recycle Box (VRB) on Bangkok city. The organic waste data analyzed on statistics of correlation and forecasting with statistic numerical modelling. Pearson’s correlation of this research is technique to measure correlation between interested data, but not causation. The forecasting techniques of this research are the Moving average, the Weight moving average, the Simple exponential smoothing, the Holt’s exponential smoothing. The amount of organic waste that produced in 2016 until 2019. Calculating Pearson’s Correlation Coefficient., the correlation between fruit peel and food waste is 0.2853 which has weak correlation between those two ingredients for producing bio fermented water. And the correlations between bio fermented water and both fruit peel and food waste are 0.2518 and 0.0877 respectively, which mean bio fermented water and fruit peel have a weak correlation, but bio fermented water and food waste have no correlation. There are 4 forecasting techniques which are 1) Moving Average k=3, 2) Weight Moving Average k=3, 3) Simple Exponential Smoothing, and 4) Holt’s Exponential Smoothing. All of techniques seem to be similar in March until December of 2020 due to the amount of food waste in year 2018 until early of 2019 is stable. But in January and February of 2020, Moving Average was calculated from past 3 years data and in January of 2016 the amount of food waste was extremely high at almost 1,200 kilograms which make an effect to the forecasting value in January of 2020. The research result benefits from Pearson’s correlation and The forecasting techniques of this research with the Moving average, the Weight moving average, the Simple exponential smoothing, the Holt’s exponential smoothing can be used to prepare for what will happen in the future, gain the valuable in insight, and thee result from prediction methods could decrease cost for the environmental management on the organic waste.